Giant hepatic hemangioma: An unusual cause of gastric compression - Özdemir, Egemen; Akbulut, Sami; Kutlutürk, Koray; Yılmaz, Sezai (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Özdemir E, Akbulut S, Kutlutürk K, Yılmaz S. Giant hepatic hemangioma: An unusual cause of gastric compression. Turk J Gastroenterol 2019; 30(10): 930-1.